2007
DOI: 10.1002/ajmg.a.32016
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of Cornelia de Lange syndrome in Europe

Abstract: Cornelia de Lange syndrome (CdLS) is a multiple congenital anomaly/mental retardation syndrome consisting of characteristic dysmorphic features, microcephaly, hypertrichosis, upper limb defects, growth retardation, developmental delay, and a variety of associated malformations. We present a population-based epidemiological study of the classical form of CdLS. The data were extracted from the database of European Surveillance of Congenital Anomalies (EUROCAT) database, a European network of birth defect registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 47 publications
2
81
1
4
Order By: Relevance
“…5 As with many studies of rare disorders, one of the main shortcomings of this work is the paucity of identified human mutations in this region. However, these mutations were identified from the collective efforts of our groups and others who have published on CdLS, representing 8 CdLS research groups and nearly 900 patients (Bhuiyan et 47 this represents an evaluated population of nearly 70 million individuals. Without coordinated global efforts, it is unlikely that higher saturation of NIPBL will be obtained.…”
Section: Clinical Features Of Patientsmentioning
confidence: 99%
“…5 As with many studies of rare disorders, one of the main shortcomings of this work is the paucity of identified human mutations in this region. However, these mutations were identified from the collective efforts of our groups and others who have published on CdLS, representing 8 CdLS research groups and nearly 900 patients (Bhuiyan et 47 this represents an evaluated population of nearly 70 million individuals. Without coordinated global efforts, it is unlikely that higher saturation of NIPBL will be obtained.…”
Section: Clinical Features Of Patientsmentioning
confidence: 99%
“…Cornelia de Lange syndrome is a congenital disorder characterized by physical abnormalities and dysmorphology, which has been associated with varying levels of intellectual disability (Barisic et al, 2008;Oliver, Arron, Sloneem, & Hall, 2008). Individuals with Cornelia de Lange syndrome often engage in repetitive and invariant behaviours that serve no apparent social function, which are generally referred to as stereotypy in the research literature (e.g., body rocking, hand flapping, mouthing, tapping; Oliver, Sloneem, Hall, & Arron, 2009;Moss, Oliver, Arron, Burbidge, & Berg, 2009).…”
Section: Assessment and Treatment Of Stereotypy In An Individual Withmentioning
confidence: 99%
“…The syndrome has also been called Brachmann de Lange, as was Dr. Brachmann in 1916 who described similar symptoms in one patient [4]. The estimated incidence varies from 1/10.000 to 1/100.000 live births [5]. Virtually all cases are sporadic but may occur following an autosomal dominant pattern [6].…”
Section: Introductionmentioning
confidence: 96%